Diverse Chemical Scaffolds Enhance Oligodendrocyte Formation by Inhibiting CYP51, TM7SF2, or EBP. Issue 4 (18th April 2019) - Allimuthu, Dharmaraja; Hubler, Zita; Najm, Fadi J.; Tang, Hong; Bederman, Ilya; Seibel, William; Tesar, Paul J.; Adams, Drew J.
Summary: Small molecules that promote oligodendrocyte formation have been identified in "drug repurposing" screens to nominate candidate therapeutics for diseases in which myelin is lost, including multiple sclerosis. We recently reported that many such molecules enhance oligodendrocyte formation not by their canonical targets but by inhibiting a narrow range of enzymes in cholesterol biosynthesis. Here we identify enhancers of oligodendrocyte formation obtained by screening a structurally diverse library of 10, 000 small molecules. Identification of the cellular targets of these validated hits revealed a majority inhibited the cholesterol biosynthesis enzymes CYP51, TM7SF2, or EBP. In addition, evaluation of analogs led to identification of CW3388, a potent EBP-inhibiting enhancer of oligodendrocyte formation poised for further optimization. Highlights: A small-molecule screen identified novel enhancers of oligodendrocyte formation Most top compounds target cholesterol biosynthesis enzymes CYP51, TM7SF2, or EBP Evaluation of analogs identified CW3388 as a potent, selective EBP inhibitor CW3388 is poised for further optimization toward EBP-targeting remyelinating drugs Abstract : Demyelinating diseases are characterized by oligodendrocyte loss. A small-molecule screen uncovered novel enhancers of oligodendrocyte formation. Most hits inhibit a narrow range of enzymes in the cholesterol biosynthesis pathway. Structure-activity relationship studies identified CW3388, a potent EBP inhibitor poised for optimization as a remyelinating therapeutic.